Improving EAP-TLS performance using cryptographic methods - Shojaie, Bahareh (IEEE, 2012)
This study is conducted to study and compare two types of Extensible Authentication Protocol-Transport Layer Security (EAP-TLS) in order to provide an alternative technique using robust cryptographic methods. Alternative EAP-TLS uses Elliptic Curve Digital Signature Algorithm (ECDSA) and Secure Hash Algorithm (SHA-256) to provide robust security and high performance. The alternative method and employed mechanisms are fully described, and compared to main EAP-TLS method. The results show the alternative algorithm provides strong security, high speed, and more efficiency with approximately same level of memory usage compared to main EAP-TLS.